Analysis of the first 2645 registrations at the research registry®: A global repository for all study types involving human participants. (December 2018) - Fowler, Alexander J.; Dowlut, Naeem; Limb, Richard; Baldacchino, Martinique Vella; Sonagara, Vinay; George, Natalie; Thavayogan, Rachel; Gundogan, Buket; Limb, Christopher; Jafree, Daniyal J.; Agha, Riaz A.
Abstract: Background: The Declaration of Helsinki has called for the registration of all research studies involving human participants. Despite this, prior registries did not allow registration certain study types, or retrospective registration. The Research Registry ® (www.researchregistry.com ) was established in 2015 to provide a venue of registration for any study involving human participants. Methods: and analysis: This retrospective database analysis describes the first 3000 registrations received by the Research Registry ® . Since the launch of the Registry in 2015, we have collected data on each registration and excluded inappropriate registrations through a weekly curation process. The characteristics of all studies registered is presented. Each registration was marked against a quality score by two researchers acting independently, and we describe how this has changed over time. No ethical approval was required for this data only study including no human participants. Results: Of 3000 registrations, we included 2645 that were submitted to the registry between February 2015 and October 2017. The number of registrations increased year on year, and we now receive between 60 and 80 registrations per month. One fifth of registrations were from China (537 [20.3%]). Retrospective observational studies were most commonly registered (1125 [42.5%]), and studies included in excess of 20 million patients (median 80 [IQR:25–200]). The quality score of registrations improved over the time (Kruskal-Wallis p < 0.05), and the 'control/comparator' component of the quality score was most poorly completed (completed by 1199 [54%]). Conclusion: The Research Registry ® has received registrations on over 2500 registrations, including in excess of 20 million patients, with the quality of registrations improving over time. Retrospective observational studies and case series are the most commonly registered. Highlights: In excess of 20 million patients have been registered with included studies. These studies come from 116 countries, the commonest being China. Quality of registrations have improved over time.